Unhealthy sport sponsorship at the 2017 AFL Grand Final: a case study of its frequency, duration and nature - Tegan Nuss; Maree Scully; Melanie Wakefield; Helen Dixon (Australian and New Zealand Journal of Public Health, 2019)
Abstract Objective: To assess the frequency, duration and nature of unhealthy marketing during the highest‐rating sporting event in Australia in 2017. Methods: A content analysis of the 2017 Australian Football League (AFL) Grand Final television broadcast identified episodes of unhealthy food and sugary drink, alcohol and gambling marketing (and pro‐health marketing as a comparison). Results: There were 559 unhealthy marketing episodes (47 minutes 17 seconds). Most (81%) were for unhealthy food and sugary drink products, while alcohol (9%) and gambling (10%) were less frequent. The total duration of unhealthy marketing was delivered primarily via fixed advertising (55%), dynamic advertising (32%) and branded objects (11%). For unhealthy food and sugary drinks, at least one episode was visible 25% of the time. For each of alcohol and gambling, at least one episode was visible 4% of the time. Unhealthy food and sugary drink marketing peaked in Quarter 2. Pro‐health marketing was limited, with 26 episodes (2 minutes 59 seconds). Conclusions: The 2017 AFL Grand Final broadcast featured a high frequency and extensive duration of unhealthy marketing, especially for unhealthy food and sugary drink brands. Implications for public health: Findings strengthen evidence supporting calls to increase regulation of sport sponsorship by unhealthy brands.